2016
DOI: 10.1037/xlm0000185
|View full text |Cite
|
Sign up to set email alerts
|

A shape-based account for holistic face processing.

Abstract: Faces are processed holistically, so selective attention to 1 face part without any influence of the others often fails. In this study, 3 experiments investigated what type of facial information (shape or surface) underlies holistic face processing and whether generalization of holistic processing to nonexperienced faces requires extensive discrimination experience. Results show that facial shape information alone is sufficient to elicit the composite face effect (CFE), 1 of the most convincing demonstrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 78 publications
3
40
0
Order By: Relevance
“…Consistent with this dual-route hypothesis, holistic processing of faces can be reduced or eliminated by disrupting object-based grouping of facial parts, despite humans having life-long experience in individuating faces (Curby et al, 2013;Zhao et al, 2016b).…”
Section: Two Influential Hypotheses Have Been Proposed To Explain Whamentioning
confidence: 59%
See 4 more Smart Citations
“…Consistent with this dual-route hypothesis, holistic processing of faces can be reduced or eliminated by disrupting object-based grouping of facial parts, despite humans having life-long experience in individuating faces (Curby et al, 2013;Zhao et al, 2016b).…”
Section: Two Influential Hypotheses Have Been Proposed To Explain Whamentioning
confidence: 59%
“…In accordance with the declaration of 1 Our sample size is primarily based on previous studies in the literature and our own research using the same paradigm (e.g., Zhao et al, 2014;2016a, 2016b. A priori power analysis using G*Power 3 (Faul, Erdfelder, Lang, & Buchner, 2007) indicated that a total number of 48 participants (24 per group) are required to detect an interaction between holistic processing and face type, with a medium effect size ηp 2 = .06 (or f = .25), α = .025, power (1-β) = .90, and correlations among measures ρ = .30 (based on a meta-analysis; .…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations